2018
DOI: 10.1111/ejh.13159
|View full text |Cite
|
Sign up to set email alerts
|

The elusive and heterogeneous pattern of type 2M von Willebrand disease: A diagnostic challenge

Abstract: Only PFA100, RIPA and VWF:RCo were always abnormal. We thus propose a minimal diagnostic test battery: RIPA (demonstrating the defective VWF-platelet interaction), VWF:Ag (exploring VWF synthesis), and VWF:CB and its ratio (to explore multimer patterns). Other tests would only serve for confirmation, if necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…PFA-100 is extensively studied in patients with (suspected) VWD. 17 18 19 21 22 23 24 26 27 28 29 30 31 32 33 34 35 36 37 43 51 52 53 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 Favaloro et al reported an overall sensitivity of 83.2% and 91.5% of the ADP and EPI cartridge respectively in a review in 2008. 79 A current analysis including all articles published before and after 2008 yielded similar test performance outcomes, as shown in Fig.…”
Section: Results Of the Point-of-care Tests In Patients With Heredita...mentioning
confidence: 99%
“…PFA-100 is extensively studied in patients with (suspected) VWD. 17 18 19 21 22 23 24 26 27 28 29 30 31 32 33 34 35 36 37 43 51 52 53 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 Favaloro et al reported an overall sensitivity of 83.2% and 91.5% of the ADP and EPI cartridge respectively in a review in 2008. 79 A current analysis including all articles published before and after 2008 yielded similar test performance outcomes, as shown in Fig.…”
Section: Results Of the Point-of-care Tests In Patients With Heredita...mentioning
confidence: 99%